Integration of the land ice model (CISM) in the Norwegian Earth System Model (NorESM) - He, Yanchun; Born, Andreas; Langebroek, Petra (Zenodo, 2019)
The fate of Greenland’s future is still largely uncertain. As many uncertainties strongly depend on the climate influencing the ice sheet, modelling communities (e.g. NCAR) use substantial resources for integrating dynamic ice sheet models into Earth System Models. Because it is largely based on CESM2, NorESM2 contains a fully functional state-of-the-art land ice model (CISM). Since it was unclear how well this model performs within NorESM, we proposed to explore the capabilities of the integrated CISM-NorESM2 system. We tested and documented the current computational set-up and numerical performance, and compared the simulated Greenland Ice Sheet characteristics to observations and a high-resolution regional model.